(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Diabetes has been considered globally as a paradigmatic chronic disease, affecting millions of people of all ages. It is an emerging chronic disease that significantly impacts patients’ quality of life. Objective: To assess the levels of knowledge, attitudes and practices on diabetes mellitus among rural residents of Sylhet, Bangladesh. Methods: A hospital-based cross-sectional study was directed among the conveniently selected 183 out-patients aged ≥18 years who were clinically diagnosed with diabetes mellitus and interviewed through a pre-tested semi-structured questionnaire in the purposively selected hospital named Moulvibazar 250 Bed District Sadar Hospital, Sylhet, Bangladesh. Results: The mean knowledge score was 4.3±2.2, attitude was 4.0±1.6 and practices were 1.8±1.8. Most rural individuals had poor knowledge (53.6%), average attitudes (54.6%) and poor practices (63.4%) on DM. The knowledge scores were statistically significant with the attitude and practice scores (P<0.05). Within the knowledge, attitude and practice scores, there was also a statistically significant correlation present (P<0.05). There were also a statistically significant effects for knowledge and attitude levels on their practice levels (P<0.05). Conclusion: On the basis of the study findings, participants had average attitudes but low levels of diabetes mellitus knowledge and practice. JAFMC BangladesH, Vol 21, No 1 (June) 2025:36-43